Efeitos jurídicos da parentalidade socioafetiva pelo olhar da jurisprudência e sua aplicação nos cartórios de registro civil - SANTOS, Vivian da Silva Francelino (2024)
This paper analyzes the legal effects of socio-affective parenting and how it is applied in civil registry offices. The concept of the family has undergone several changes over time, with its most significant transformation following the advent of the Federal Constitution of 1988, together with the Civil Code of 2002, which expanded the concept of the Brazilian family entity. In this sense, socio-affective parenting will be analyzed in the context of the legal system with the aim of identifying how it is treated by doctrine and the courts. Documentary and bibliographical research was used, focusing on the study of doctrine specializing in Family Law and on case law and decisions handed down by the different Brazilian Courts. Thus, this work aims to point out the developments regarding socio-affective parenting, explaining all the concepts and requirements that circulate around it, as well as how it is applied in extrajudicial proceedings and its legal effects.